Racial Harassment, Ethnic Concentration and Economic Conditions - Christian Dustmann; Ian Preston; Francesca Fabbri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2004)
We analyze the association between concentration of minorities and local economic conditions on the one side, and racial harassment and hostile majority attitudes on the other. We distinguish the formation of hostile attitudes and the realization of acts of racially motivated violence as distinct processes and find strong evidence for this. We develop a framework that subsumes and structures many existing theories on attitude formation and acts of harassment. Our measures of harassment include both direct reports and precautionary behaviour. Our data sources are the fourth National Survey of Ethnic Minorities for the UK and the 1981 and 1991 UK Census.
Keywords: J15; R23; 330; Attitudes; Economics of Minorities